Towards a Global Administrative Space in Environmental Governance? How Global Administrative Network Structures Shape Environmental Policy Outputs - Jörgens, H.; Kolleck, N.; Bruna Rodrigues; Keith Goldstein (ECPR General Conference 2025, 2025)
The paper discusses the concept of a "global administrative space" in environmental governance, focusing on two treaty systems: the UNFCCC and the CBD. Using survey data and social network analysis, we examine policy-oriented cooperation and information exchange among over 1,000 organizations involved in these frameworks environmental policy networks. Key findings include: 1. There is evidence of the emergence of a global environmental administrative space characterized by networks of international public administrations, national and sub-national bureaucracies, NGOs, businesses, and research institutions. This administrative space facilitates collaboration and knowledge sharing, thereby contributing to the formulation and implementation of global environmental policies. 2. International public administrations, especially the UNFCCC and CBD secretariats, occupy central positions within these transnational climate and biodiversity policy networks. Their involvement is characterized by substantial bureaucratic autonomy combined with a high level of integration with administrative and non-administrative actors across different governance levels. 3) The presence and roles of organizations differ between the climate and biodiversity policy networks, with NGOs demonstrating varying degrees of integration. While private sector involvement is less pronounced in these networks, organizations like the International Union for Conservation of Nature (IUCN) exhibit dual characteristics (both NGO and IO), suggesting complexity in the organizational landscape of global environmental governance. This study contributes to the broader understanding of how structural features of global administrative networks shape environmental policy.